Bridging cultural divides: family support and psychological resilience as catalysts for student adaptability in Sino-foreign cooperative education - Yan, Yiwen; Mahdi, Moudi; He, Yuan (Frontiers in Psychology, 2025)
IntroductionWith the rapid advancement of educational internationalisation, Sino-foreign cooperative education has become a vital mechanism for reform, though students’ insufficient cross-cultural adaptability poses a significant challenge to their academic excellence and international skill acquisition.MethodsThis study randomly selected and surveyed 402 students from eight Sino-foreign cooperative educational projects in Chengdu, utilising structural equation modelling to investigate the factors affecting student adaptability.ResultsThe findings reveal that family support has a significantly positive impact on students’ cross-cultural adaptability, with psychological resilience acting as a key intermediate variable in this relationship. This underscores the critical combination of external aids and internal psychological assets.DiscussionConsequently, it is suggested that a family-based support system be established, and psychological education alongside cross-cultural training be enhanced to bolster students’ psychological resilience and adaptive capacity. Furthermore, the management of these joint programs should be improved to cultivate international talents who are well-adapted to the demands of socio-economic advancement.